Genetic evaluation of growth rate and efficiency-related traits in Menz sheep - Bisrat, A.; Besufkad, S.; Abebe, A.; Goshme, S.; Abebe, A.; Zewdie, T.; Areaya, A.; Tesema, Z.; Demis, C.; Yitagesu, E.; Wondifra, Y.; Asfaw, T.; et al. (Public Library of Science, 2025)
Growth efficiency traits are economically important and their genetic improvement is essential in small ruminants, particularly under conditions of limited feed availability. Data on body weights of Menz sheep collected from 2009 through 2023 in Menz sheep community-based breeding programs (CBBPs) were used to estimate genetic parameters for six months weight (WT6), average daily gain from birth to weaning (ADG1), average daily gain from weaning to six months (ADG2), and average daily gain from six months to yearling (ADG3), and corresponding kleiber ratios (KR1, KR2, KR3), efficiency of growth (GE1, GE2, GE3), and relative growth rate (RGR1, RGR2, RGR3). Least-squares analysis was performed using the PROC GLM procedure in SAS 9.4. (Co)variance components and corresponding genetic parameters were estimated using the Average Information Restricted Maximum Likelihood (AI-REML) method in WOMBAT software by fitting six univariate animal models that incorporated various combination of direct additive, maternal genetic, and permanent environmental effects. The year of birth, season and villages of CBBP contributed significantly (P < 0.001) to the variation of all the considered traits. The model with direct additive genetic effect alone provided the best fit for all traits except WT6 and ADG1, for which the model including direct and maternal genetic effects performed best. Direct heritability estimates (h2a) were 0.46 ± 0.02, 0.44 ± 0.02, 0.35 ± 0.02, 0.21 ± 0.02, 0.38 ± 0.02, 0.36 ± 0.02, 0.23 ± 0.02, 0.39 ± 0.02, 0.39 ± 0.02, 0.48 ± 0.03, 0.36 ± 0.02, 0.42 ± 0.02, and 0.47 ± 0.03 for WT6, ADG1, ADG2, ADG3, KR1, KR2, KR3, GE1, GE2, GE3, RGR1, RGR2, and RGR3, respectively. Maternal heritability (h2m) for WT6 and ADG1 was 0.02 ± 0.01 and 0.02 ± 0.01. Moderate to high direct heritability estimates for the studied traits revealed that direct selection would be yield significant genetic progress. Genetic correlation estimates between the traits raged from −0.66 for ADG1-RGR2 and KR1-RGR2 to 0.98 for KR2-RGR2. Traits measured within the same growth period showed strong positive genetic and phenotypic correlations. Since Menz sheep are raised under harsh environmental conditions, incorporating efficiency related traits into the selection program can enhance the overall efficiency of the breeding program. Selection for WT6 would be more effective and increase efficiency-related traits due to their positive genetic correlations.